Dynamic commissural splint - Nair Chandrasekharan; Sivagami G; Kunnekel Ashish; Naidu Munirathnam (Wolters Kluwer Medknow Publications, 2008)
Microstomia, an abnormally small oral orifice, can manifest as a sequela of burns involoving the oral and perioral tissues due to contraction of the tissues and hypotonia of the circumoral musculature. Regardless of the etiology, scar contracture results in deformities that produce esthetic and functional impairment. Changes in the circumoral anatomy prevent optimal dental care and maintenance of good oral hygeine. The anatomic changes may detrimentally alter eating, speech, and mandibular motion. Prosthetic treatment involves providing physical resistance to scar contracture by maintaining the oral commisssures in their normal relationship by means of a splint. This article describes a method to fabricate a dynamic commissural splint and decribes its use in two cases.